Clinical indicators for pulmonary arterial hypertension in thalassemia - Chueamuangphan N. (2014)
Objective: To explore clinical indicators for pulmonary arterial hypertension (PAH) in thalassemia (Thal). Material and Method: A study was conducted in thalassemia patients at Chiang Rai Hospital, Chiang Rai, Thailand. Pulmonary artery systolic pressure (PASP) was determined by doppler echocardiography and PAH was defined as PASP > 35 mmHg. Patient characteristics were extracted from medical records. Characteristics of patients with and without PAH were compared. Risk indicators were explored with logistic regression analysis. Results: Two hundred twenty four patients were included, 144 E/β-Thal, 37 homozygous β-Thal and 43 Hb H disease. There were 65 patients (29.0%) with PAH, 53 (81.5%) with E/β-Thal, 8 (12.3%) with homozygous β-Thal and 4 (6.2%) with Hb H disease. In a multivariable analysis, features significantly associated with PAH were E/β-Thal (OR = 1.98, 95% CI; 1.29-3.01) and post splenectomy status (OR = 2.36, 95% CI; 1.17-4.73). Conclusion: Significant indicators for PAH in thalassemia were E/β-Thal and post splenectomy status.